PERAN GURU DALAM PERSFEKTIF KEPEMIMPINAN PENDIDIKAN - Marjuni, A. (Inspiratif Pendidikan, 2019)
Teachers are professional educators with the main task of educating, teaching, guiding, directing, training, evaluating, and evaluating students in early childhood education through formal education, basic education and secondary education. Thus, the teacher is a professional in carrying out its functions, both educating, teaching, directing, training, assessing and evaluating student participants. The teacher is the foremost force in opening the horizons of students entering the world of science and the world of society where they will implement what is obtained from their teacher and their practice. Teachers are professions that prepare human resources to welcome the nation’s development in filling independence. Teachers with all their abilities and efforts to prepare learning for students. So it is not wrong if we place teachers as one of the keys to nation-building into a developed nation in the future. Educational leadership is the ability to drive the implementation of education, so that educational goals that have been set can be achieved effectively and efficiently.